Road Safety Evaluation Framework for Accessing Park Green Space Using Active Travel - Luo, Yuanyuan; Liu, Yanfang; Xing, Lijun; Wang, Nannan; Rao, Lei (Frontiers in Environmental Science, 2022)
The Covid-19 pandemic has led to the burgeoning demand for active travel (walking or cycling) which is known as a healthy, pollution-free, and affordable daily transportation mode. Park green space (PGS) as an open natural landscape become a popular destination for active travel trips in metropolitan area. Pedestrians and cyclists are often at high crash risk when exposed to complicated traffic environments in urban areas. Therefore, this study aims to propose a safety assessment framework for evaluating active travel traffic safety (ATTS) from the perspective of urban planning and exploring the impact of the point-of-interest (POI) aggregation phenomenon on ATTS. Firstly, the links between ATTS and the built environment variables were investigated and integrated into the framework using Catastrophe model. Secondly, the relationship between the POI density and ATTS was investigated using three spatial regression models. Results in the Wuhan Metropolitan Area as a case study show that: (1) Population density, road density, nighttime brightness, and the vegetation situation near PGS have pronounced impacts on ATTS. Pedestrians enjoy safer road facilities than cyclists. (2) Among the four park categories, using active travel to access Theme Parks is the safest. (3) Density of hospital and restaurant near PGS are negatively correlated with ATTS, while the residence and school densities have a positive correlation. The safety framework can be applied in other regions because the selected built environment indicators are common and accessible. The findings offer appropriate traffic planning strategies to improving the safety of active travel users when accessing PGS.